Pengaruh pelaksanaan supervisi dan implementasi manajemen mutu pendidikan terhadap kompetensi profesional guru Yayasan Pendidikan Gema Nusantara Kabupaten Tangerang - Siti Maesaroh; Jaka Slameta; Rika Nurhidayah (Universitas Tangerang Raya, 2023)
Improving the quality of education in schools requires professional and systematic education to achieve its targets. This is because improving the quality of education at a micro level is largely determined by management operations at the school level. National education development is a joint effort of all components of government and society. Education can produce educated people who have an important role in social transformation in society. Teacher professional competence refers to the combination of knowledge, skills, attitudes and behavior required to carry out teacher duties effectively and efficiently in an educational context. This involves a deep understanding of the subject being taught, effective teaching methods, the ability to communicate well, as well as the ability to adapt to changes and challenges in the world of education. Educators are professional staff who are tasked with planning and implementing the learning process, assessing learning outcomes, providing guidance and training, as well as conducting research and community service, especially for educators in higher education.